THE WESTWARD DRIFT OF THE LITHOSPHERE: A ROTATIONAL DRAG? - Scoppola B.; Boccaletti D.; Bevis M.; Carminati E.; Doglioni C. (My University, 2006)
Net westward rotation of the lithosphere relative to the underlying mantle is a controversial phenomenon first attributed to tidal effects, and later to the dynamics of mantle convection. In spite of a number of independent geological and geophysical arguments for westward tectonic drift, this phenomenon has received little recent attention. We suggest that this differential rotation is a combined effect of three processes: (1) tidal torques act on the lithosphere generating a westerly directed torque decelerating Earth's spin; (2) the downwelling of the denser material toward the bottom of the mantle and in the core slightly decreases the moment of inertia and speeds up Earth's rotation, only partly counterbalancing the tidal drag; (3) thin (3-30 km) layers of very low viscosity hydrate channels occur in the asthenosphere. It is suggested that shear heating and the mechanical fatigue self-perpetuate one or more channels of this kind, which provide the necessary decoupling zone of the lithosphere. © 2006 Geological Society of America.
Keywords: EARTH'S ROTATION; ASTHENOSPHERE VISCOSITY; DECOUPLING; LITHOSPHERE; WESTWARD DRIFT